Backpressure adjustable gas turbine combined cycle: A method to improve part-load efficiency. (15th October 2018) - Li, Yongyi; Zhang, Guoqiang; Bai, Ziwei; Song, Xiaowei; Wang, Ligang; Yang, Yongping
Highlights: Backpressure adjustable gas turbine combined-cycle is proposed. Off-design characteristics with different operation strategies are analysed. Load range with strategy keeping turbine inlet temperature constant is expanded. Part-load efficiency is improved with a maximum increase of 0.52–1.76%. Abstract: Nowadays, power demand and supply of the power grid fluctuate constantly for the increasing proportion of the renewable energy. Improving the operation performance of the gas turbine combined cycle (GTCC) power plant at part-load conditions is becoming a very critical problem. An innovative combined cycle solution, called backpressure adjustable gas turbine combined cycle (BAGTCC) with corresponding operation strategies, is proposed in this paper to improve off-design performance by adjusting turbine backpressure. The off-design calculation models of the combined cycle are built and their reliability is verified. The feasibility of this scheme is analyzed with the Mach number of the gas flow in turbine. Then, the part-load operation characteristics of the topping cycle, bottoming cycle and combined cycle of the GTCC and BAGTCC, operating with two different operation strategies respectively, are analyzed and compared. The simulation results show that, the proposed BAGTCC can broaden the load range, where turbine inlet temperature (TIT) maintains its design value, from 100–82.4% to 100–63.7%. The combined cycle efficiency has been improved significantly in that load range, up by 0–0.52 and 0–1.76 percentage points over the two conventional operation strategies respectively. Furthermore, this solution has the ability to adjust the power distribution of topping and bottoming cycle, which means that the heat-to-electric ratio can be adjusted when the bottoming cycle is involved in heating. The energy saving potential of BAGTCC can be increased by broadening the compressor flow adjustment range. In conclusion, backpressure regulating is an efficient method to improve the part-load efficiency of the GTCC.